PREVALENCE OF GASTROINTESTINAL HELMINTHS IN SHEEP FROM CENTRAL KORDOFAN, SUDAN (Journal of Veterinary Medicine and Animal Production, 2022)
A total of 498fecal samples and 45 gastrointestinal tracts of sheep from Central Kordofan were examined for gastrointestinal helminths. Mixed helminth infections were found to be common in 91.1% of gastrointestinal tracts examined. Nematode infections were the commonest, reaching 82.2% of the examined animals. Haemonchus contortus and Trichostrongylus colubriformis were, having the highest prevalence 68.9% and 60%, respectively. Other identified nematode species were Cooperia pectinata, Oesophagostomum columbianum, Strongyloides papillosus, Trichuris globulosa and Skrjabinema oviswith a frequency of 35.1%, 59.2%, 62.2%, 27% and 8.1, respectively. Cestodes were recovered in 57.8% of the gastrointestinal tracts. The identified species were Stilesia globipunctata, Avitellina centripunctata, Moniezia expansa and Moniezia benedeni. The most prevalent cestode species were S. globipunctata and A. centripunctata with a frequency of 37.8% for each species. There was a seasonal effect on nematode infection in sheep as judged by egg output and worm burden. Both parameters showed their highest levels during the rainy season
Keywords: Prevalence; gastrointestinal; helminthes; sheep